Direito civil punitivo: do dano moral punitivo à idealização de uma causa geral de multa civil - Feijó, Arthur Nogueira (2015)
The purpose of this paper is to critically examine, through a civil and a constitutional law point of view, the punitive aspect intoned in Brazilian civil liability. In this sense, initially, a survey of basics of Law General Theory is done, emphasizing the sanction institute, to join the study of civil responsibility functions. Then, directs the study for the compensation by moral damage, which is justified because on it is found the jurisprudential cradle where born, on home land, the idea of punitive damages, culminating with a critical view on the compatibility of the punitive element with homeland civil systematic. Among the conclusions, it is discussed the need to respect the order of legality for imposing punitive sanctions, even in civil law, which is why it points to the illegality of the Brazilian jurisprudential construction regarding the punitive connotation given to the penalty resulting from moral damages. Continuing, without joining in the analysis of the punitive reason justice but on the premise that the order of punishment, under a functionalist view, demonstrates usefulness in the role of law to order conducts, prelude to a legal model, based on the idea that a general cause of civil fine, in which it idealizes a possible new punitive system in civil law and in accordance with the constitutional imperatives, imbued with the goal of effectiveness of the jurisdiction and illicit prevention. The methodology adopts a model dedicated to bibliographic and jurisprudential research (with emphasis on the Superior Court of Justice), under the support of an open discourse, encouraging the reflection of the concepts presented is privileged and a proposal about a modification of the existing civil systematic is presented, which, far from the intention to enter into new dogmas, it directs to the desire to attract attention to an issue that has taken on greater complexity and relevance today,